An Inhibitor of Casein Kinase 1ε/δ (PF670462) Prevents the Deterioration of Dextran Sodium Sulfate-induced Ulcerative Colitis Caused by UVB Eye Irradiation - Hiramoto, Keiichi (Int J Biol Sci, 2018)
Although we previously reported the exacerbation of dextran sodium sulfate (DSS)-induced ulcerative colitis by ultraviolet (UV) B eye irradiation, we do not yet understand the mechanism behind this phenomenon. In this study, we examined the relationship between the deterioration of DSS-induced ulcerative colitis and clock genes. We induced a mouse model of ulcerative colitis by administering DSS for 5 days, and administered UVB eye irradiation on each day of the DSS treatment period. The DSS-induced ulcerative colitis was deteriorated by the UVB eye irradiation. The levels of Clock, brain and muscle arnt-like protein 1 (Bmal1), reverse orientation c-erb A gene (Rev-Erb)α, RAR-related orphan receptor gamma (RORγt), and interleukin (IL)-17 in the colon were increased by UVB eye irradiation in the DSS-treated mice (UVB/DSS-treated mice). Conversely, the nuclear factor, interleukin 3 regulated (NFIL-3) levels in the colon were lower after UVB eye irradiation. The Casein Kinase 1ε/δ inhibitor (PF670462) administration, which is a Clock/Bmal1 inhibitor (PER2 activator), inhibited the deterioration caused by UVB eye irradiation. These results suggest that the UVB eye irradiation-mediated exacerbation of DSS-induced ulcerative colitis depends on IL-17 produced in response to alterations in clock genes.